Can a Government Enhance Long-Run Growth by Changing the Composition of Public Expenditure? - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper ;, 2013)
This paper studies the effects of public expenditure reallocations on long-run growth. To do this, we assemble a new dataset based on the IMF's GFS yearbook for the period 1970-2010 and 56 countries (14 low-, 16 medium-, and 26 high-income countries). Using dynamic panel GMM estimators, we find that a reallocation involving a rise in education spending has a positive and statistically robust effect on growth, when the compensating factor remains unspecified or when this is associated with an offsetting reduction in social protection spending. We also find that public capital spending relative to current spending appears to be associated with higher growth, yet results are non-robust in this latter case.